Struktur dan Fungsi Sosial Ungkapan Larangan Masyarakat di Kanagarian Pasir Baru - Pertiwi Pertiwi; Zulfadhli Zulfadhli (Faculty of Languages and Arts, Universitas Negeri Padang, 2020)
The Minangkabau community has long been known for its oral tradition. Through this, advice, manners and social values are integrated from generation to generation. One variety of this tradition is the expression of prohibitions. This study aimed to describe the structure of people’s belief in prohibition expressions about the human body and medicines in Kanagarian Pasir Baru; the social function of oral tradition in the form of prohibition expressions about the human body and medicines in Kanagarian Pasir Baru. This type of research is a qualitative study using descriptive methods. Data in this study were obtained from interviews with the native speakers. The steps of data collection can be categorized as follows: data inventory, preliminary analysis, recording, transliteration, interviews and reporting. The results of the analysis indicate the structure of prohibition expressions about the human body and medicines in Kanagarian Pasir Baru was divided into two forms, namely two parts and three parts. Moreover, the social function of people's belief in prohibition expressions about the human body and medicines such as a) the belief enhancement function, b) the imaginary projection system, c) the educational function, d) the inhibit function, and e) the entertainment function.